Mastery learning in recorder playing: a focus on posture and breathing / Peter Ong ... [et al.] - Peter Ong; Abdul Latif, Fauzila; Nik Latif, Nik Hartini; Abd Razak, Rozaina; Ong, Eng Tek; Jamaludin, Putri Aimin Amirah (College of Creative Arts, 2025)
The research investigates how mastery learning influences novice recorder players by studying essential elements of posture and breathing which form the basis for musical instruction and tone sound production. A research project with 70 Year 3 novice recorder learners who were new to playing the recorder applied a quasi- experimental design. The researcher divided 70 Year 3 recorder students into two separate groups of 35 students each for this study. The study used quantitative methods which included both preliminary and final evaluation assessments used to measure posture and breathing results. The analysis utilized independent samples t- tests together with one-way ANOVA resulting in significant statistical outcomes. Through the mastery learning intervention the experimental group students achieved meaningful improvements in their posture and breathing compared to the control group. Mastery learning in recorder education provides an exceptional teaching method that strengthens essential musical skills for year 3 students to build strong foundations for advanced musical training.